Adjusted Permutation Method for Multiple Attribute Decision Making with Pruning Solution Approach - Ali Athari Beyragh (Journal of Global Pharma Technology, 2017)
Permutation method is one of the multi-critera decision making techniques which can get the best order of the given alternatives to have the best benefits. This method solves the decision making problem by calculation the benefit of each possible permutation with N Factorial calculations for N alternatives. In this paper, we presented a new method for improving the classical permutation method. It works with pruning the possible permutation sequences of the alternatives to reach the best solution. Our method can solve the problem by less than N(N-1)/2 calculations. It tries to find the best order by comparing the effect of switching the places of two nearby alternatives in the permutation sequences.Keywords: Multi-criteria Decision Making, Adjusted Permutation, Pruning.